Description Ability Literacy Science Numeracy in Class VIII Students at SMP IT Wahdah Islamiyah Makassar - Rifda Nur Hikmahwati Arif; Rifda Mardian Arif; Salma Samputri (PT ARRUS Intelektual Indonesia, 2024)
This research is a descriptive research with survey method. The purpose of this study was to determine the level of Numeration Literacy Ability of grade VIII students at SMP IT Wahdah Islamiyah Makassar. The population of this study was all grade VIII students at SMP IT Wahdah Islamiyah Makassar consisting of 3 classes with a total of 89 students. The sample was selected by saturated sampling technique so that the determination of the sample when all members of the population were used as samples and the number of research samples was 89 students. The research instruments are in the form of numeracy literacy ability test question instruments totaling 15 questions and critical thinking skills test questions totaling 15 questions. The data collection technique is by giving tests directly. The data were analyzed by descriptive statistical analysis techniques. Based on the results of the analysis, it can be concluded that 1) The level of numeracy literacy ability of students has an average value of 30.34 fsn is in the low category. 2) The level of critical thinking ability of students has an average score of 39.78 and is in the low category.